Massive cold cloud clusters. Issue Volume 12:Issue S316(2015) (31st March 2017) - Toth, L. Viktor; Zahorecz, Sarolta; Marton, Gabor; Ristorcelli, Isabelle; Juvela, Mika; Montier, Ludovic; Bernard, Jean-Philippe
Abstract: The all-sky Planck catalogue of Galactic Cold Clumps (PGCC) allows an almost unbiased study of the early phases of star-formation in our Galaxy. Several thousand of the clumps have also distance estimates allowing a determination of mass and density. The nature of Planck cold clumps varies from IRDCs to tiny nearby cold clouds with masses ranging from one to several tens of thousands solar masses. Some of the clumps are embedded in GMCs, others are isolated. Some are close or even very close to OB associations, while others lay far from any UV luminous objects. The small scale clustering of nearby PGCCs was studied with the improved Minimum Spanning Tree (MST) method identifying groups in 3D space, locating also massive cold cloud clusters eg. PGCCMST G210.6-19.5 in LDN 1641.